Pemberdayaan Dan Pengembangan Industri Kecil Menengah Pabrik Tempe Dan Tahu - Putri, Shofi Rahmadannia; Gayatri, Ida Ayu Made Er Meytha; Febriansa, M. Rahman; Wagini, Wagini; Mulyana, Andi (Universitas Dehasen Bengkulu, 2024)
Most Indonesian people really like tempeh and tofu. The affordable price means these two foods always sell well on the market. However, behind the cheap prices of tempeh and tofu there are entrepreneurs who are having difficulty because the price of soybeans continues to soar. If the price of tempeh and tofu increases, it is feared that purchases of tempeh and tofu will decrease. However, if it is not increased, entrepreneurs will have difficulty in the production process. The aim of this service is to optimize MSME income through market improvement.